Cognitive Principles in Online Learning: Improving Student Motivation and Achievement - Mansour As- Siddiqy; Fatim Nur Nuainy (PT Mutiara Bustan Ilmu, 2026)
This study investigates the application of cognitive principles in online learning and their influence on student motivation and academic achievement. The research employed a qualitative library research design using a descriptive-analytical approach. Data were collected from journal articles, books, conference papers, and scholarly publications related to cognitive science, online learning, and educational psychology. The data were analyzed through thematic content analysis to identify major themes and relationships among cognitive principles, motivation, and learning outcomes. The findings indicate that cognitive principles such as cognitive load management, retrieval practice, metacognition, and self-regulated learning significantly contribute to improving student engagement and academic performance. Effective instructional design, timely feedback, and meaningful social interaction also enhance motivation and learning achievement in online environments. The study concludes that integrating cognitive science into online instruction can create more effective, learner-centered, and engaging learning experiences. These findings provide practical implications for educators and policymakers in developing evidence-based strategies to improve the quality of online education.